Bandwidth Enhancement using Polymeric Grid Array Antenna for Millimeter-Wave Application - Wan Asilah, Wan Muhamad; Razali, Ngah; Mohd Faizal, Jamlos; Ping, Jack Soh; Mohd Tarmizi, Ali (Springer, 2017)
A new grid array antenna designed on a polymeric polydimethylsiloxane (PDMS) substrate is presented. A good relative permittivity of the PDMS substrate increases the antenna bandwidth. The PDMS surface is also hardened to protect the proposed grid array antenna’s radiating element. A SMA coaxial connector is used to feed the 36 × 35 mm2 antenna from its bottom. A bandwidth enhancement of 72.1% is obtained compared to conventional antenna. Besides, its efficiency is increased up to 70%. The simulated and measured results agreed well and the proposed antenna is validated to suit millimeter-wave applications.